Light removes inactivation of the A-type potassium channels in scallop hyperpolarizing photoreceptors - Shimatani, Y (J Neurosci, 1995)
The properties of light-activated and voltage dependent conductances in the hyperpolarizing photoreceptors of the isolated retina of the giant scallop (Patinopecten yessoensis) have been studied in whole-cell voltage-clamp recordings. Resting membrane potential of the cells was - 35 to -60 mV in the dark. Large outward current was maintained during illumination when the cell was voltage clamped at the resting potential. Previous reports have shown that the hyperpolarizing response to light and the light-activated outward current are mediated by an increase of a conductance of K+ channels in the plasma membrane (Gorman and McReynolds, 1974; Gomez and Nasi, 1994a). This report shows that the light-activated K+ channels of this photoreceptor cell generate the voltage-dependent transient outward current in response to depolarizing voltage steps in the dark. The characteristic of this current resembles the typical voltage-dependent transient current (A- current) of molluscan neurons in the kinetics of activation and inactivation, and in the blockage by 4-aminopyridine (4-AP). However, the voltage-dependent transient current during illumination becomes a flat stable form which inactivation process disappeared. We report here that light removes inactivation of the K+ channels which generate the voltage-dependent transient outward currents in the dark.